Eastern Caribbean Currency Union : 2022 Article IV Consultation with Member Countries on Common Policies of the Eastern Caribbean Currency Union-Press Release; Staff Report; and Statement by the Executive Director for the Eastern Caribbean Currency Union. (IMF Staff Country Reports; Country Report ;, 2022)
With ECCU economies slowly emerging from the pandemic with scars, the impact of the war in Ukraine is a setback to the nascent recovery. Higher food and energy prices, amid ongoing supply disruptions and intra-regional transportation bottlenecks, are raising inflation, eroding income, lowering output growth, worsening fiscal and external positions, and threatening food and energy security. As a result, inflation is expected to hover over 51/2 percent in 2022. Real GDP is projected to grow by 71/2 percent in 2022, leaving output still well below the pre-pandemic level. Fiscal deficits are projected to remain sizable, given continued pandemic- and disaster-related spending and temporary support to address rising living costs, thereby keeping gross financing needs and public debt at elevated levels in the near term. The financial system has remained broadly stable so far, with adequate capital and liquidity buffers, but nonperforming loans remain high and could rise further following the expiration of the ECCB's loan moratoria program. The outlook is subject to large downside risks, primarily from further increases in commodity prices and new COVID variants amid vaccine hesitancy, in addition to the ever-present threat of natural disasters.